Comprehensive transcriptome profiling of BET inhibitor-treated HepG2 cells - Baek, Mina; Chai, Jin Choul; Choi, Hae In; Yoo, Eunyoung; Binas, Bert; Lee, Young Seek; Jung, Kyoung Hwa; Chai, Young Gyu (PLOS ONE, 2022)
Hepatocellular carcinoma (HCC) is the most common primary liver cancer and poor prognosis. Emerging evidence suggests that epigenetic alterations play a crucial role in HCC, suggesting epigenetic inhibition as a promising therapeutic approach. Indeed, the bromodomain and extra-terminal (BET) inhibitors inhibit the proliferation and invasion of various cancers but still lack a strong mechanistic rationale. Here, we identified the differentially expressed mRNAs (DEmRNAs) and lncRNAs (DElncRNAs) in human HCC cell line HepG2 treated with the BET inhibitors, JQ1, OTX015, or ABBV-075. We analyzed the correlation between DEmRNAs and DElncRNAs in common for the three inhibitors based on their expression profiles and performed functional annotation pathway enrichment analysis. Most of these shared DEmRNAs and DElncRNAs, including some novel transcripts, were downregulated, indicating decreased proliferation/adhesion and increased apoptosis/inflammation. Our study suggests that BET proteins play a crucial role in regulating cancer progression-related genes and provide a valuable resource for novel putative biomarkers and therapeutic targets in HCC.